Quantitative MRI assessment of peripheral nerves - S. N. Morozova; D. A. Grishina; V. A. Orlov; S. I. Kartashov; V. V. Sinkova; D. S. Tsaregorodtsev; M. V. Krotenkova; N. A. Suponeva (Нервно-мышечные болезни)
Over the past decade magnetic resonance imaging is being increasingly used in revealing pathological changes in peripheral nervous system due to a number of technical innovations and growth of diagnostical strength, and, therefore, due to initiation of research of several magnetic resonance imaging methods which allow to perform quantitative assessment of peripheral nerves. Among them, diffusion tensor magnetic resonance imaging which gives an opportunity to investigate microstructural changes in nerves tissue by water diffusion evaluation should be mentioned first. T2‑relaxometry and magnetization transfer ratio studies allow assessing macromolecular integrity of peripheral nerves elements. Chemical shift‑based fat fraction evaluation in peripheral nerves and corresponding muscles is also of great scientific interest both for diagnostic and therapy effect monitoring purposes. Manuscript presents brief description of above‑ mentioned methods, as well as recent results and perspectives of their application for peripheral nerves evaluation, supplemented with own illustrations of experimental observations.